Pengembangan Model Pelatihan Berbasis Mixed Reality Pada Program K3 Bagi Mahasiswa Pendidikan Vokasi Fakultas Teknik Universitas Negeri Makassar - Haryoko, Sapto; Jaya, Hendra; Risal, Ahmad; Bahar, Muh. Mahdinul (Seminar Nasional LP2M UNM, 2025)
Abstrak. The purpose of this study was to develop a Mixed Reality (MR)-based training model for Occupational Health and Safety (OHS) in vocational education, specifically for students of the Faculty of Engineering, Universitas Negeri Makassar. This development research employed the Research and Development (R&D) approach, consisting of the stages of needs analysis, design, development, implementation, and evaluation. The MR training model was developed through the creation of interactive simulation scenarios that integrate real and virtual environments to support students' understanding of OHS procedures. Expert validation was conducted to assess the model’s feasibility, followed by limited trials involving vocational students to obtain empirical feedback on usability and learning effectiveness. The results of expert validation indicated that the MR-based training model was categorized as highly valid, with an overall mean score of 3.82 across indicators including construction, content, language, interactivity, technical performance, and procedural accuracy. Student responses also showed highly positive perceptions, where more than 90% of participants agreed or strongly agreed that the implementation of Mixed Reality enhanced their understanding of OHS procedures, improved readiness before practice, facilitated independent learning, and increased engagement during training sessions. The MR simulations provided a safe, immersive, and risk-free learning environment that supported the development of OHS competencies. In conclusion, the Mixed Reality–based training model developed in this study is feasible, effective, and recommended for broader implementation in vocational education. The model significantly improves students’ comprehension of OHS concepts, strengthens risk identification skills, and supports active and independent learning. It is also recommended that institutions enhance supporting infrastructure and expand scenario development to maximize the benefits of MR-based training in OHS programs.Kata Kunci: Mixed Reality, Keselamatan dan Kesehatan Kerja (K3), Pendidikan Vokasi, Model Pelatihan, Simulasi Interaktif.